Lactobacilli as Anti-biofilm Strategy in Oral Infectious Diseases: A Mini-Review - Giordani, Barbara; Parolin, Carola; Vitali, Beatrice (Frontiers in Medical Technology, 2021)
The spread of biofilm-related diseases in developed countries has led to increased mortality rates and high health care costs. A biofilm is a community of microorganisms that is irreversibly attached to a surface, behaving very differently from planktonic cells and providing resistance to antimicrobials and immune response. Oral diseases are an excellent example of infection associated with the formation of highly pathogenic biofilms. It is generally accepted that, when the oral homeostasis is broken, the overgrowth of pathogens is facilitated. Among them, Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans are the main etiological agents of periodontitis, while Streptococcus mutans is strongly associated with the onset of dental caries. Other microorganisms, such as the fungus Candida albicans, may also be present and contribute to the severity of infections. Since the common antibiotic therapies usually fail to completely eradicate biofilm-related oral diseases, alternative approaches are highly required. In this regard, the topical administration of probiotics has recently gained interest in treating oral diseases. Thus, the present mini-review focuses on the possibility of using Lactobacillus spp. as probiotics to counteract biofilm-mediated oral infections. Many evidence highlight that Lactobacillus living cells can impede the biofilm formation and eradicate mature biofilms of different oral pathogens, by acting through different mechanisms. Even more interestingly, lactobacilli derivatives, namely postbiotics (soluble secreted products) and paraprobiotics (cell structural components) are able to trigger anti-biofilm effects too, suggesting that they can represent a novel and safer alternative to the use of viable cells in the management of biofilm-related oral diseases.